A Population Pharmacokinetic Approach to Describe Cephalexin Disposition in Adult and Aged Dogs - Ana Paula Prados; Paula Schaiquevich; Verónica Kreil; Agustina Monfrinotti; Pamela Quaine; Lisa Tarragona; Ruben Hallu; Marcela Rebuelto (Veterinary Medicine International)
This study was conducted in order to characterize the pharmacokinetics of orally administered cephalexin to healthy adult and aged dogs, using a population pharmacokinetic approach. Two hundred and eighty-six cephalexin plasma concentrations obtained from previous pharmacokinetic studies were used. Sex, age, pharmaceutical formulation, and breed were evaluated as covariates. A one-compartment model with an absorption lag-time (Tlag) best described the data. The final model included age (adult; aged) on apparent volume of distribution (Vd/F), apparent elimination rate (ke/F), and Tlag; sex (female; male) on ke/F, and breed (Beagle; mixed-breed) on Vd/F. Addition of the covariates to the model explained 78% of the interindividal variability (IIV) in Vd/F, 36% in ke/F, and 24% in Tlag, respectively. Formulation did not affect the variability of any of the pharmacokinetic parameters. Tlag was longer, whereas Vd/F and ke/F were lower in aged compared to adult animals; in female aged dogs ke/F was lower than in male aged dogs; however, the differences were of low magnitude. Different disposition of cephalexin may be expected in aged dogs.